Pengaruh Variasi Tebal Magnet Terhadap Nilai Back EMF dan Ke pada Pemodelan PMSG 12S8P - Rohmad Mucharom; Bayu Aji Saputro; Veryn Resvia Dhena (Universitas Islam Raden Rahmat, Malang, 2023)
The use of new and renewable energy must be the main concern of the Indonesian government to realize clean, environmentally friendly energy. One of the new renewable energies that has great potential in the world, including in Indonesia, and which has not yet been maximized, is wind energy. Micro-scale power plants are one of the ways to utilize energy sources that can be used to support the distribution of the electrification program in Indonesia. One type of generator for electricity source technology from renewable energy that can be developed is the Permanent Magnet Synchronous Generator (PMSG). This research was carried out by varying the thickness of the magnet on PMSG 12S8P. The experimental method was carried out by modeling simulation on Infolytica MagNet software. The variation of the thickness of the magnet used in the experiment was 3mm, 6mm, 9mm with a speed of 1000rpm. From several variations of the simulation experiment, it is known that the thickness of the magnet can affect the density and distribution of the flux and its value is directly proportional to the thickness of the magnet. The thicker the magnet, the higher the Back EMF and Ke Constant values.